The Influence of Work Ethic, Work Culture, and Organizational Support on Employee Performance Through Motivation as an Intervening Variable Among Employees of the Religious Court in Gorontalo Province - Ibrahim, Meimoon; Yakup, Yakup; Usu, Idrus; Said, Dian (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to analyze the influence of work ethic, work culture, and organizational support on employee performance, with work motivation as an intervening variable among employees of the Religious Court in Gorontalo Province. The population in this study consists of 120 employees from the Religious Court offices in Gorontalo Province. The analysis method used is path analysis. The results indicate that work ethic, work culture, and organizational support have a positive and significant impact on employees' work motivation. Additionally, work ethic, work culture, and organizational support also have a positive and significant effect on employee performance, demonstrating that a conducive work environment can enhance productivity. Work motivation itself has a positive impact on employee performance, meaning that the higher the work motivation, the better the performance achieved. Furthermore, work motivation serves as a mediating variable in the relationship between work ethic, work culture, and organizational support on employee performance. This finding suggests that the combination of these factors, along with high work motivation, further strengthens improvements in employee performance at the Religious Court in Gorontalo Province.